Moroccan pre-service elementary teachers: attitudes toward STEM education and mobile devices - Amaaz, Aziz; Mouradi, Abderrahman; Erradi, Moahamed; Allouch, Ali (Institute of Advanced Engineering and Science, 2024)
The purpose of this study was to explore Moroccan pre-service elementary teachers' attitudes toward integrated science, technology, engineering, and mathematics (STEM) education and the use of mobile devices in integrated STEM education. The research sample was selected using convenience sampling. Data were collected from 226 pre-service teachers in the Bachelor of Education Elementary Specialty (BEES) using a 28-item questionnaire. The validity of the items was tested by factor analysis using the extraction method of principal component analysis with varimax rotation. Reliability tests for the different constructs were conducted by calculating Cronbach's alpha. Frequency, mean, standard deviation and Mann-Whitney tests were used to analyze the data. The results revealed that pre-service elementary teachers have generally neutral attitudes toward integrated STEM education, and they also showed that pre-service teachers' attitudes toward integrated STEM education do not depend on gender or grade level. However, these attitudes are dependent on pre-university studies. Pre-service teachers with a scientific background have significantly more positive attitudes toward integrated STEM education than their counterparts with a literary background. Furthermore, the results of this study also revealed that pre-service teachers have positive attitudes toward the use of mobile devices in integrated STEM education, and these attitudes are not dependent on gender, grade level, or pre-university studies.